THE RELATIONSHIP OF SELF EFFICACY WITH STUDENT MATHEMATICS LEARNING OUTCOMES THROUGH THE CONCRETE-PICTORIAL-ABSTRACT (CPA) APPROACH IN PRIMARY SCHOOLS - Aan Yuliyanto; Turmudi Turmudi; Mubiar Agustin; Idat Muqodas; Hafiziani Eka Putri (JPSD (Jurnal Pendidikan Sekolah Dasar), 2020)
Abstract. The low self-efficacy (SE) and student learning outcomes (LO) are the backgrounds of this study. This research is to see the relationship between SE and LO students through the Concrete-Pictorial-Abstract (CPA) approach. The research method used is quasi-experimental, with nonequivalent pretest-posttest control group design in mathematics learning of 119 elementary students in Purwakarta, Subang, Karawang, and Bekasi. The instrument uses a description test and attitude scale. The results of the analysis show that there is no relationship between the achievement and increase of students' SE and LO with the value of R on the achievement and increase of SE and LO respectively 0.044 and 0.053 and significance> 0.05.Keywords: Concrete-Pictorial-Abstract (CPA) approach, Self-Efficacy (SE), Learning Outcomes (LO)